Diversity of Local Tawangmangu Bananas: Traditional Markets as Learning Resources for High School Biology - Yoshia, Selumiel; Hanik, Nur Rokhimah (Jurnal Biologi Tropis, 2026)
Biodiversity learning in senior high schools (SMA) is often less than optimal due to a lack of local context. Tawangmangu boasts a diverse range of banana varieties in its traditional markets, which offer potential as a biology learning resource in line with the existing curriculum. This study aims to identify and analyze the diversity of local banana varieties in Tawangamngu Tourist Market and develop biology learning resources for high school biodiversity. Sampling was conducted using a purposive-random method across all market stalls. Morphological identification was conducted systematically, including visual documentation, measurements of quantitative (fruit length, diameter, number of clusters) and qualitative (skin color, fruit shape, flesh texture, aroma) parameters, and interviews with vendors to obtain ethnobotanical information. Data were verified with taxonomic literature and then analyzed through triangulation of morphological observations, ethnobotanical interviews, and literature references. The research identified 17 banana varieties with the AA, AAA, AAB, ABB, and BB genome groups, including Bawen, Raja Bulu, Susu, Cavendish, Raja Sereh, Raja Uli, Raja Mas, Ambon Lumut, Ambon Kuning, Tanduk, Kepok Kuning, Kepok Putih, Mas Kirana, Nangka, Klutuk, and Kembung. Each variety has distinctive morphological characteristics and different uses. The diversity of local bananas at Tawangmangu Tourist Market can be used as an effective learning resource for high school biodiversity materials, bridging theoretical concepts with students' real-world environments, in accordance with the Independent Curriculum framework.